The O-C2 angle established at occipito-cervical fusion dictates the patient’s destiny in terms of postoperative dyspnea and/or dysphagia - Izeki, Masanori (Springer Berlin Heidelberg, 2013)
PURPOSE: We have revealed that the cause of postoperative dyspnea and/or dysphagia after occipito-cervical (O-C) fusion is mechanical stenosis of the oropharyngeal space and the O-C2 alignment, rather than total or subaxial alignment, is the key to the development of dyspnea and/or dysphagia. The purpose of this study was to confirm the impact of occipito-C2 angle (O-C2A) on the oropharyngeal space and to investigate the chronological impact of a fixed O-C2A on the oropharyngeal space and dyspnea and/or dysphagia after O-C fusion. MATERIALS AND METHODS: We reviewed 13 patients who had undergone O-C2 fusion, while retaining subaxial segmental motion (OC2 group) and 20 who had subaxial fusion without O-C2 fusion (SA group). The O-C2A, C2–C6 angle and the narrowest oropharyngeal airway space were measured on lateral dynamic X-rays preoperatively, when dynamic X-rays were taken for the first time postoperatively, and at the final follow-up. We also recorded the current dyspnea and/or dysphagia status at the final follow-up of patients who presented with it immediately after the O-C2 fusion. RESULTS: There was no significant difference in the mean preoperative values of the O-C2A (13.0 ± 7.5 in group OC2 and 20.1 ± 10.5 in group SA, Unpaired t test, P = 0.051) and the narrowest oropharyngeal airway space (17.8 ± 6.0 in group OC2 and 14.9 ± 3.9 in group SA, Unpaired t test, P = 0.105). In the OC2 group, the narrowest oropharyngeal airway space changed according to the cervical position preoperatively, but became constant postoperatively. In contrast, in the SA group, the narrowest oropharyngeal airway space changed according to the cervical position at any time point. Three patients who presented with dyspnea and/or dysphagia immediately after O-C2 fusion had not resolved completely at the final follow-up. The narrowest oropharyngeal airway space and postoperative dyspnea and/or dysphagia did not change with time once the O-C2A had been established at O-C fusion. CONCLUSIONS: The O-C2A established at O-C fusion dictates the patient’s destiny in terms of postoperative dyspnea and/or dysphagia. Surgeons should pay maximal attention when establishing the O-C2A during surgery, because their careless decision for the O-C2A may cause persistent dysphagia or a life-threatening consequence. We recommend that the O-C2A in O-C fusion should be kept at least at more than the preoperative O-C2A in the neutral position.